2017
DOI: 10.1111/sum.12363
|View full text |Cite
|
Sign up to set email alerts
|

Does variable rate irrigation decrease nutrient leaching losses from grazed dairy farming?

Abstract: The irrigation of grazed dairy pastures can be highly profitable, but can lead to the enhanced leaching of nitrogen (N) and phosphorus (P) and impairment of freshwater quality. A six‐year study was conducted to determine whether the use of variable rate irrigation (VRI), compared to uniform rate irrigation (URI), could decrease N and P leaching losses from a 143‐ha area under intensively grazed dairy cattle that had been partly hydrologically isolated by the installation of artificial drainage pipes. Median co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…The extent of soil variability can differ between farms, so assessment of the benefits has to be on a case-by-case basis. The use of VRI, compared with uniform or fixed applications, can lead to improved grain yield and water use efficiency (Sharp & Hedley 2018), and reduced nutrient losses and irrigation water applied (McDowell 2017;Drewry et al 2019). When compared with fixed application and scheduling of irrigation water, Drewry et al (2019) showed, for three Hawke's Bay case study farms, that VRI reduced water applied by 66% to Drewry et al, Maximising the value of irrigation through improved use of soil resources and sensor technology…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of soil variability can differ between farms, so assessment of the benefits has to be on a case-by-case basis. The use of VRI, compared with uniform or fixed applications, can lead to improved grain yield and water use efficiency (Sharp & Hedley 2018), and reduced nutrient losses and irrigation water applied (McDowell 2017;Drewry et al 2019). When compared with fixed application and scheduling of irrigation water, Drewry et al (2019) showed, for three Hawke's Bay case study farms, that VRI reduced water applied by 66% to Drewry et al, Maximising the value of irrigation through improved use of soil resources and sensor technology…”
Section: Resultsmentioning
confidence: 99%
“…Variable rate irrigation (VRI) systems enable the variable application of irrigation water or other inputs, e.g. fertiliser, reducing drainage and nutrient losses compared with uniformly applied irrigation water (McDowell 2017;Drewry et al 2019). There is a need to provide farmers with new tools that enable further improvements to productivity, efficiency of water use on-farm, and reduced environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Under spray irrigation, the potential for overland flow should be minimal, but substantial P exports can occur via subsurface flow, especially if the soil has a poor capacity to adsorb P or irrigation practice is poor. In a study in Central Otago, New Zealand, P exported in subsurface drainage was measured for 3 yr under a uniform rate irrigation from a sandy‐textured soil (anion storage capacity <20%) (McDowell, 2017). Exports decreased by 70% following soil mapping and the recalibration of water application rates to match soil types beneath the irrigator.…”
Section: Implications For Fertilizer Good Management Practicesmentioning
confidence: 99%
“…Two further papers explore the relationship between nutrients and water-related issues, with Boitt et al (2018) considering the phosphorus cycle but approached more from the perspective of irrigation in New Zealand, whereas Harris et al (2018) consider the effect of drainage on the plant community, and C and N cycling in permanent grassland. The importance of these interactions is repeated in a paper in SUM by McDowell (2017), who analysed data from a 6-year study and demonstrated that variable-rate irrigation decreased nutrient leaching losses of intensively grazed dairy pastures and advocates that wider adoption could decrease farm leaching losses compared with other irrigated areas.…”
Section: A Profile Of 70 Years Of Soil Researchmentioning
confidence: 99%
“…() consider the effect of drainage on the plant community, and C and N cycling in permanent grassland. The importance of these interactions is repeated in a paper in SUM by McDowell (), who analysed data from a 6‐year study and demonstrated that variable‐rate irrigation decreased nutrient leaching losses of intensively grazed dairy pastures and advocates that wider adoption could decrease farm leaching losses compared with other irrigated areas.…”
mentioning
confidence: 99%